Decolonization of Human Anterior Nares of Staphylococcus aureus with Use of a Glycerol Monolaurate Nonaqueous Gel - Patrick M. Schlievert (American Society for Microbiology, 2020)
ABSTRACT Staphylococcus aureus is a highly significant infection problem in health care centers, particularly after surgery. It has been shown that nearly 80% of S. aureus infections following surgery are the same as those in the anterior nares of patients, suggesting that the anterior nares is the source of the infection strain. This has led to the use of mupirocin ointment being applied nasally to reduce infections; mupirocin resistance is being observed. This study was undertaken to determine whether gel composed of 5% glycerol monolaurate solubilized in a glycol-based, nonaqueous gel (5% GML gel) could be used as an alternative. In our study, 40 healthy human volunteers swabbed their anterior nares for 3 days with the 5% GML gel. Prior to swabbing and 8 to 12 h after swabbing, S. aureus and coagulase-negative staphylococcal CFU per milliliter were determined by plating the swabs on mannitol salt agar. Fourteen of the volunteers had S. aureus in their nares prior to 5% GML gel treatment, most persons with the organisms present in both nares; five had pure cultures of S. aureus. All participants without pure culture of S. aureus were cocolonized with S. aureus and coagulase-negative staphylococci. Five of the S. aureus strains produced the superantigens commonly associated with toxic shock syndrome, though none of the participants became ill. For both S. aureus and coagulase-negative staphylococci, the 5% GML gel treatment resulted in a 3-log-unit reduction in microorganisms. For S. aureus, the reduction persisted for 2 or 3 days. IMPORTANCE In this microflora study, we show that a 5% glycerol monolaurate nonaqueous gel is safe for use in the anterior nares. The gel was effective in reducing Staphylococcus aureus nasally, a highly significant hospital-associated pathogen. The gel may be a useful alternative or additive to mupirocin ointment for nasal use prior to surgery, noting that 80% of hospital-associated S. aureus infections are due to the same organism found in the nose. This gel also kills all enveloped viruses tested and should be considered for studies to reduce infection and transmission of coronaviruses and influenza viruses.